2017
DOI: 10.1007/978-981-10-4304-8_12
|View full text |Cite
|
Sign up to set email alerts
|

The IGF1-PI3K-Akt Signaling Pathway in Mediating Exercise-Induced Cardiac Hypertrophy and Protection

Abstract: Regular physical activity or exercise training can lead to heart enlargement known as cardiac hypertrophy. Cardiac hypertrophy is broadly defined as an increase in heart mass. In adults, cardiac hypertrophy is often considered a poor prognostic sign because it often progresses to heart failure. Heart enlargement in a setting of cardiac disease is referred to as pathological cardiac hypertrophy and is typically characterized by cell death and depressed cardiac function. By contrast, physiological cardiac hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
57
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 154 publications
1
57
0
Order By: Relevance
“…Previous studies have shown that physiological cardiac hypertrophy is associated with an exerciseinduced increase in the levels of IGF-1 (Neri Serneri et al, 2001). We found that the cardiomyocyte surface area in response to IGF-1 for 48 hours was significantly larger than that of the non-stimulated H9C2 cells, and the levels of hypertrophy markers (ANP and BNP) were also significantly increased in mRNA levels, while leaving aactin mRNA unchanged, which is considered as a trigger for physiological cardiac hypertrophy (McMullen and Izumo, 2006;Weeks et al, 2017). Autophagy is a highly conserved and ubiquitous metabolic pathway in living organisms (Sandoval et al, 2008).…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies have shown that physiological cardiac hypertrophy is associated with an exerciseinduced increase in the levels of IGF-1 (Neri Serneri et al, 2001). We found that the cardiomyocyte surface area in response to IGF-1 for 48 hours was significantly larger than that of the non-stimulated H9C2 cells, and the levels of hypertrophy markers (ANP and BNP) were also significantly increased in mRNA levels, while leaving aactin mRNA unchanged, which is considered as a trigger for physiological cardiac hypertrophy (McMullen and Izumo, 2006;Weeks et al, 2017). Autophagy is a highly conserved and ubiquitous metabolic pathway in living organisms (Sandoval et al, 2008).…”
Section: Discussionmentioning
confidence: 69%
“…The results of our study help to generate hypotheses to be tested in future studies. It is known that signaling pathways and molecular mechanisms responsible for mediating pathological versus physiological cardiac hypertrophy induced by long‐term exercise training are different (Weeks, Bernardo, Ooi, Patterson, & McMullen, ). The insulin‐like growth factor 1 ( IGF1 ) signaling pathway regulates exercise‐induced physiological cardiac hypertrophy and cardiac protection (Weeks et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that signaling pathways and molecular mechanisms responsible for mediating pathological versus physiological cardiac hypertrophy induced by long‐term exercise training are different (Weeks, Bernardo, Ooi, Patterson, & McMullen, ). The insulin‐like growth factor 1 ( IGF1 ) signaling pathway regulates exercise‐induced physiological cardiac hypertrophy and cardiac protection (Weeks et al, ). Tereshchenko et al recently identified a GEH‐associated genetic polymorphism in the intron of the IGF1 ‐receptor ( IGF1R ) gene (Tereshchenko et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…IGF1 is associated with the process of cardiac hypertrophy closely and substantial essays have indicated that it is an active regulator in cardiac hypertrophy. IGF1‐PI3K‐Akt signaling pathway has been manifested to regulate cardiac hypertrophy (Weeks et al, 2017). In this study, we found that IGF1 served as a downstream target of miR‐182‐5p.…”
Section: Discussionmentioning
confidence: 99%